VD_FINDINFO HC / 2012 / 219 vom 30. März 2012 - VD Tribunal cantonal (2012)
RECONNAISSANCE DE LA DÉCISION, DÉCLARATION D'EXÉCUTION | 39 par. 1 CL (2007), 53 CL (2007), 309 let. a CPC (CH), 319 let. a CPC (CH), 322 al. 1 CPC (CH), 327a CPC (CH), 335 CPC (CH), 45 al. 2 CDPJ